THE POLARITY OF LAW AND FREEDOM IN PAULINE RELIGION - Pathrapankal, Joseph (Journal of Dharma, 1980)
Looking for a sensible and correct assessment of the relevance and future of religions, I came across the two following quotations, and, I think, they spell out the dynamics of our discussions about religions: The future of religion is connected with the possibility of developing a faith in the possibilities of human experience and human relationships that will create a vital sense of the solidarity of human interests and inspire action to make that sense a reality. (John Dewey). No creed is final. Such a creed as mine must grow and change as knowledge grows and changes. (Sir Arthur Keith). The implied idea in these quotations is that religions have to undergo a process of change and re-making if they have to exercise any influence on humanity.